Gypsums reuse in dental mechanics laboratories to reduce waste generation. - Puentes Castillo, Jairo Humberto; Daza Rico , Benjamín (SATHIRI, 2021)
The gypsums used to make denture impressions in dental mechanics laboratories generate large amounts of waste with one-time molds and are then discarded and turned into waste. The study was carried out at the Autonomous University Corporation of Nariño, with the aim of determining the appropriate techniques in the recovery of dental gypsums, promoting their reuse, to obtain a sustainable model and reduce the generation of dental solid waste. It was sought to establish the volumes of dental waste generated in the laboratories, by carrying out laboratory tests that made it possible to determine the optimal techniques for the recovery of the material and to analyze the characteristics of the materials obtained to determine their possible uses. The applied methodology was experimental, with a mixed approach; in order to identify various uses for the residual gypsum generated. Through laboratory and field tests, alternative processes were determined that made it possible to reduce and reuse this residual material. Trials were carried out to verify its use as an adjuvant of fertilizers in the crops of the orchard in the IV Division of the National Army of Apiay (Meta), carrying out a pilot test there and verifying its usefulness in soils destined for agricultural use. Other tests were carried out with plants of timber species for reforestation, obtaining favorable results regarding the growth of the fertilized plants. It was concluded that the recovered gypsum is suitable to be used as soil fertilizers, in fruit and vegetable crops and in land used for reforestation.
Keywords: gypsums; setting; reuse; calcining; crushing